A hybrid fuzzy logic-based MPPT algorithm for PMSG-based variable speed wind energy conversion system on a smart grid - S. Karthikeyan; C. Ramakrishnan (Energy Storage and Saving)
Recently, wind power has gained popularity as a sustainable energy source. Wind energy conversion systems (WECSs) can accept fixed speed and variable speed (VS) operations. VS-WECSs are preferable to conventional WECSs because of their higher electricity collection capacity. Maximum power point tracking (MPPT) systems are essential for maximizing the efficiency of wind energy generation in wind turbine (WT) installations linked to power grids. This study introduces a hybrid fuzzy logic controller-based MPPT (FLC-MPPT) for WTs connected to permanent magnet synchronous generators (PMSGs) to accurately determine the maximum power output of WTs. This study employs a three-phase back-to-back converter to link a PMSG to a utility grid. The reference signals for pulse width modulation controllers comprise two-phase system currents. It constructs a converter that can transfer electrical energy in both directions using insulated-gate bipolar transistor technology and is powered by a battery. The machine-side converter uses model predictive control for the present control loop. Given the generator’s susceptibility to changes in wind conditions, this factor is of the utmost importance. A WT simulation was conducted using MATLAB/Simulink and an FLC methodology was employed. The model used a PMSG. Measurements of rotor speed, power, induced voltage, and current were taken in relation to variations in wind speed. The simulation results show that the FLC-MPPT can maximize the output power over a wide range of wind speeds with a higher efficiency of 92.6% and performance of 95.7%.